PERAN STRATEGIS PEMERINTAH DAERAH DALAM MENINGKATKAN KESADARAN MASYARAKAT TERHADAP KEAMANAN SIBER - Anggi Anggraeni Kusumoningtyas; Selentinus Gunawan; Rizkia Ramadhan; Mu'min Aziz; Dinar Paradisa (Ensiklopedia Research and Community Service Review, 2025)
This Community Service Program (PKM) titled "The Strategic Role of Local Government in Increasing Public Awareness of Cybersecurity" was carried out in Terumbu Village, Kasemen District, Serang City, Banten. The program aims to strengthen the role of local governments in educating the public about cybersecurity and improving the digital literacy of local government apparatus. Participatory lectures, cybercrime simulations, and group discussions were applied to enhance participants' understanding of cyber threats and prevention measures. Results indicate a significant increase in awareness, with local officers expressing readiness to continue periodic cybersecurity education. This program highlights the effectiveness of collaborative, localized approaches between local governments and academics in fostering a secure, inclusive, and empowered digital culture.Kata Kunci: cybersecurity, digital literacy, local government, public education, pentahelix collaboration